2022
DOI: 10.1007/s11113-022-09731-5
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Assisted Reproductive Technology Live Births in the United States

Abstract: As postponement of first births continues in the United States, women and couples will likely continue to turn to assisted reproductive technologies (ART) to overcome biological barriers to childbearing. This paper uses stochastic projections to estimate the potential impacts of ART on the US total fertility rate (TFR) overall and across sociodemographic groups using publicly available data. Assuming the trends in ART continue and the TFR remains at the mean estimate, the projection shows the ART TFR will rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Most studies of the relationship between infertility and number of children have focused on the use of ART and the question of whether the use of ART is associated with increased fertility rates (Lazzari et al, 2023 ; Leridon, 2017 ; Tierney, 2022 ). The relevance of ART to the question of the association of infertility and fertility rates is based on the assumption that people who have used reproductive technology are infertile and would likely have not conceived without ART.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Most studies of the relationship between infertility and number of children have focused on the use of ART and the question of whether the use of ART is associated with increased fertility rates (Lazzari et al, 2023 ; Leridon, 2017 ; Tierney, 2022 ). The relevance of ART to the question of the association of infertility and fertility rates is based on the assumption that people who have used reproductive technology are infertile and would likely have not conceived without ART.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Demographers forecast rising demand for assisted reproductive technologies (ART) in high‐income countries owing to the increased postponement of childbearing to older ages 1,2 . Whereas live births arising from ART in the US accounted for 1.3 percent of live births in 2019, this figure represents almost a doubling relative to that of 2015 3 .…”
Section: Figurementioning
confidence: 99%
“…Previous research in Europe and the United States has mostly focused on the impact of ART on overall fertility by adopting either a period (Habbema et al, 2009;Hoorens et al, 2007;Tierney, 2022) or cohort (Leridon, 2017;Leridon & Slama, 2008;Sobotka et al, 2008) approach, with most studies showing a rather modest contribution of 2-5%. Studies that have looked at age-specific ART fertility have found that the absolute contribution of ART to the TFR often peaks in the mid-30s, while the relative share of ART births increases with age (Burcin et al, 2020;Lazzari et al, 2021;Tierney, 2022). For example, Lazzari et al, (2021) found that increases in period fertility rates at late (40 +) reproductive ages in Australia were largely driven by the increasing use of ART.…”
Section: Introductionmentioning
confidence: 99%